Prevalência e fatores associados à prevenção secundária do câncer de mama no município de Maringá - PR - Matos, Jéssica Carvalho de (2008)
Neoplasms are one of the main causes of morbidity and mortality in world population and among women breast cancer is one of that generates more concerns. The statistics estimates by year more than 1.050.000 new cases of breast cancer all over the world and the projection to 2009 in Brazil estimates 49.400 thousand new cases (50,71/100.000). The aim of this study was to make an analysis of the secondary prevention actions of breast cancer and related factors among women aged between 40 and 69 years old in the city of Maringá, Paraná State, Brazil. It was made an analytical, exploratory and transversal study as population investigation in domiciles in the city of Maringá, Paraná State, Brazil. The sample was composed by 429 women aged between 40 and 69 years old. The sampling stratified and randomized was distributed in four strata, representing geographically the position of the incidence. From each stratus was selected a simple and randomized sample proportional to the number of women who were living in each stratus. The data were collected by domiciliary interviews using a structured and previously tested questionnaire. The data were analyzed by using the SPSS software. It was made a bivariate analysis and a multiple analysis. The project was approved by the Ethics Committee at UEM. The studied population was constituted by 439 women aged between 40 and 69 years, 45,8% among 40 to 50 years, 29,6% between 51 and 60 and 24,6% between 61 and 69 years old. The predominant ethnical group was Caucasian and the most prevalent economical status was classified as C. About 33,9% made only elementary school and only 7,7% of women made full higher education studies. The majority (76,1%) of them related no use of alcoholic drinks and only 13% of women referred to smoke habits. About 62% already used contraception pills. The majority of women interviewed were classified as overweighed; the women who experienced menopause were averaged in 47 years. Only 6,1% presented breast cancer history, 69,2% never made use of hormone reposition therapy. The prevalence of routine habits to make the BSE (Breast Self-exam) of 64,5% and BCE (Breast Clinical Exam) in the last gynecological visit was of 71,5%. The prevalence of mammography revealed 79% of women who made it. The related factors to the BSE making was the social status, school background, age, menarche and the treatment of menopause. The associated variables to make BSE were: social status, scholarship, age of menarche and treatment of menopause. The following factors as age, ethnic condition, economical status, religion, age of menarche, age of menopause, number of pregnancies and treatment of menopause were associated to the mammography routine habit. The association between social and economical level and the conduct preventive habits is directly proportional that means, higher the social and economical level will be higher the number of visits made and consequently more exams requested and greater the chances to the early diagnostic. It was attested an imbalance in health attention and a lack of integrality in women assistance. This deficiency in Health System may result an inequity related to the prevention actions of breast cancer, reducing the chances of an early diagnostic and an effective treatment, consequently increasing the number of deaths by breast cancer.